Economic benefit of wildlife reintroduction: A case of elk hunting in Tennessee, USA. (1st September 2020) - Chapagain, Binod P.; Poudyal, Neelam C.
Abstract: With growing public interest in ecosystem restoration, wildlife agencies in the U.S. and around the world have adopted wildlife reintroduction program as a conservation strategy. In addition to their ecological benefits, stakeholders are often interested in economic benefits of wildlife reintroduction such as hunting opportunities once a viable population is established. Even though the trip-based travel cost models are widely used in economic valuation of hunting access, such models are not applicable in valuation of sites of recent restoration, where hunting opportunities are limited. With the case of recently completed elk restoration in Tennessee, USA, this study characterizes the economic benefit of hunting opportunity resulting from reintroduction. In doing so, it also presents a procedure to estimate the economic benefit of current use and unmet demand associated with hunting opportunities generated from a wildlife reintroduction program. The annual net economic benefit associated with current use and value of unmet demand is found to be over 2 million. The study also demonstrates the viability of permit-based models in producing reliable estimates of economic benefit of recreation access where demand is lottery-rationed or trip profile data is unavailable. Highlights: Stakeholders are interested in hunting benefits of wildlife restoration programs. Trip based travel cost model is not applicable in sites of lottery-rationed recreation. A permit-based zonal travel cost model was estimated for hunting access to NCWMA. We show the viability of permit-based models in producing reliable value estimates. Results illustrate the net benefit of hunting opportunity attributable to elk restoration.